The Use of Innovative Technologies in Increasing the Efficiency of English Teaching (Global Scientific Review, 2022)
The role and the effective usage of innovative technologies in teaching English are considered in this article. The Internet links, which are effectively used during the lessons, are also shown here. The effective use of Innovative technologies, such as computers, the Internet, multimedia resources in the educational process is the only way to show the quality of education.